The Complete Chloroplast Genome of Medinilla tapete-magicum (Melastomataceae) from Sulawesi, Indonesia - Priyadi, Arief; Kuswandi, Paramita Cahyaningrum; Yulianti, Evy; Pratiwi, Risha Amilia; Asih, Ni Putu Sri (Journal of Tropical Biodiversity and Biotechnology, 2024)
In this study, the genome of an endemic Sulawesi’s plant, Medinilla tapete-magicum was sequenced using Illumina NextSeq 500 and assembled the whole chloroplast genome. Results showed that the cpGenome is 155,602 bp in size with typical quadripartite structure of a large single copy (LSC) region (85,409 bp), a short single copy (SSC) region (16,629 bp), and a pair of inverted repeats (IRs) regions (26,782 bp). The cpGenome is composed of 132 genes, which consists of 87 protein coding genes, 37 tRNAs, and 8 rRNAs. The sliding window analyses showed that psbB-psbH and ndhF-rpl32 can potentially be used as markers. Microsatellite motifs of mononucleotide A and T dominated in the cpGenome. The phylogenetic trees from the concatenated 76 shared protein coding gene sequences showed the Medinilla clade was monophyletic and M. tapete-magicum is a sister species in the SE Asian clade which contain M. magnifica and M. speciosa.